Visualization Analysis of Dynamic Evolution of the Theme in Improvisation Studies - Peng-bin Gao; Weiwei Wu; Bo Yu (Institute of Advanced Engineering and Science, 2014)
The field of improvisation is composed of a multiplicity of topics leading to a vast array of management literature. However, the research does not provide a chronological picture of the topics it addresses, making it difficult to develop an overview of the evolution and trends in the literature. To address this issue, co-word analysis was employed to reveal patterns and trends in the improvisation field by measuring the association strengths of keywords of relevant documents. Data were collected from Web of Knowledge database for the period 1997-2012. Using the co-occurrence matrix of keywords, the results of multivariate statistical techniques show that the improvisation research involves many fields including innovation, strategy, learning, change, leadership, metaphor, entrepreneurship, capability.In order to trace the dymamic changes of the improvisation field, the whole period was further separated into three periods: 1997-2002, 2003-2007 and 2008-2012. The strategic diagram and social network analysis was used to trace the dynamic changes of the improvisation research, and results show that improvisation field has some established research themes and it also changes rapidly to embrace new themes. DOI : http://dx.doi.org/10.11591/telkomnika.v12i5.4927